High throughput and low power consumption on a wireless sensor network - Bassi, Germán Alejandro (2012)
Wireless communications are subject to fading and interferences that affect their performance. However, the broadcast nature of wireless transmissions is an advantage that has been exploited in the past to improve performance. Nodes belonging to a sensor network could listen to messages sent from other nodes and participate in this communication for the benefit of the entire network. In this paper, we present a protocol following these lines. The novelty of our approach is to obtain high throughput with low complexity and low energy consumption.